2019
DOI: 10.1155/2019/6547019
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Metformin on a Preeclampsia-Like Mouse Model Induced by High-Fat Diet

Abstract: Background Metformin has been reported to decrease insulin resistance and is associated with a lower risk of pregnancy-induced hypertension and preeclampsia. It is widely accepted that the placenta plays a crucial role in the development of preeclampsia. Our aim is to explore the effect of metformin on preeclampsia. Study Design We examined control diet-fed (isocaloric diet) pregnant mice (CTRL group), pregnant mice fed a high-fat diet (HF group), and high-fat-diet-fed pregnant mice treated with metformin (HF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…In pregnant women, the increased activity of anti-angiogenic factors induces the systemic endothelial dysfunctions and vasospasm and provokes preeclampsia [ 358 ]. MF treatment of mice with a preeclampsia-like model induced by a six-week high-fat diet (HFD) before pregnancy reduces the blood pressure, prevents the proteinuria, normalizes the fetal and maternal weight, and leads to an improvement of the placental labyrinth and fetal vascular development, impaired in the conditions of preeclampsia [ 359 ]. This is based on MF-induced normalization of placental production of MMP-2 and VEGF in preeclamptic mice, which, in turn, improves the pregnancy outcomes [ 359 ].…”
Section: Metformin and Gestational Diabetes Mellitusmentioning
confidence: 99%
“…In pregnant women, the increased activity of anti-angiogenic factors induces the systemic endothelial dysfunctions and vasospasm and provokes preeclampsia [ 358 ]. MF treatment of mice with a preeclampsia-like model induced by a six-week high-fat diet (HFD) before pregnancy reduces the blood pressure, prevents the proteinuria, normalizes the fetal and maternal weight, and leads to an improvement of the placental labyrinth and fetal vascular development, impaired in the conditions of preeclampsia [ 359 ]. This is based on MF-induced normalization of placental production of MMP-2 and VEGF in preeclamptic mice, which, in turn, improves the pregnancy outcomes [ 359 ].…”
Section: Metformin and Gestational Diabetes Mellitusmentioning
confidence: 99%
“…57 Furthermore, there is evidence that it resolves the preeclampsia phenotype in animal models. 58,59 A randomized trial by Syngelaki et al 60 examining the potential of metformin to decrease maternal and fetal weight gain in women who are obese reported a remarkable 76% reduction in rates of preeclampsia (OR, 0.24; 95% CI, 0.10e0.61; P<.001). A metaanalysis of trials assessing metformin vs insulin concluded that rates of hypertensive disorders are decreased among those administered metformin (n¼836; RR, 0.68; 95% CI, 0.48e0.95), 61 but a metaanalysis of trials where women received metformin or placebo did not find a difference in hypertensive disorders 61 (n¼609; RR, 0.86; 95% CI, 0.33e2.26; P¼.76).…”
Section: Metformin and Sulfasalazinementioning
confidence: 99%
“…As previously described in section "preeclampsia", sFlt-1 and soluble endoglin are anti-angiogenic factors implicated in the pathogenesis of preeclampsia. In a model of preeclampsia in mice fed with a high-fat diet, the use of metformin has also shown to improve maternal blood pressure and foetal outcomes [125].…”
Section: Metforminmentioning
confidence: 99%